HUBUNGAN KECEPATAN DAN KELINCAHAN DENGAN KETERAMPILAN MENGGIRING BOLA MAHASISWA PKO SEPAK BOLA UNTAN - Anuarta, Anuarta; Supriatna, Eka; Perdana, Rahmat Putra (Universitas Tanjungpura, 2025)
This research investigates the relationship between speed and agility with dribbling skills among students of the Sports Coaching Education Program at Universitas Tanjungpura who are involved in football. A quantitative descriptive approach was applied, utilizing a 30-meter sprint test to measure speed, a zig-zag run test to assess agility, and an obstacle dribbling test to evaluate dribbling skills. The participants consisted of 20 students. Normality and homogeneity analyses confirmed that the data met statistical assumptions. Linearity tests further indicated that the independent and dependent variables were linearly related. Correlation analysis demonstrated a significant association between speed and dribbling skills (r = 0.480; p = 0.032), while agility did not show a significant correlation (r = 0.234; p = 0.321). The results highlight that speed plays a stronger role in influencing dribbling performance compared to agility. Consequently, speed-focused training is suggested to enhance dribbling ability, while agility exercises remain valuable as complementary practice.